IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PROSES PENILAIAN KINERJA PEMASOK - Dian Eko Hari Purnomo; Yogi Akbar Sunardiansyah (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2021)
Supplier performance appraisal is an important decision in a company, because it will increase the company's competitiveness in the face of highly competitive business competition. PT. JQK is currently selecting suppliers who will supply mahogany wood raw materials with five suppliers, namely Manggala Jati, UD. Jati Mukti, “Mukti” Teak Wood Shop, Gunung Hijau, and Indah Sentosa. In this study, the best supplier performance assessment used the Analytical Hierarchy Process (AHP) method. This method is based on the concept of pairwise comparison for each existing hierarchy in the existing hierarchical structure. The criteria used in this selection are 3 criteria and 6 sub-criteria that support each criterion. The criteria that can be used for supplier performance assessment are time, quality, and price. Sub-criteria that can be used in evaluating supplier performance are on time delivery, lead time, specifications of raw materials, quantity of raw materials, purchase price of raw materials, and transportation costs. Based on calculations using the AHP method, the supplier with the best value is the “Indah Sentosa” supplier, whose value is 0.344 or 34.420%.